Radiation Dose Reduction During EVAR: Results from a Prospective Multicentre Study (The REVAR Study). (September 2018) - Hertault, Adrien; Rhee, Robert; Antoniou, George A.; Adam, Donald; Tonda, Hisashi; Rousseau, Hervé; Bianchini, Aurélia; Haulon, Stéphan
Abstract : Objective: To evaluate radiation exposure in standard endovascular aneurysm repair (EVAR) using intra-operative guidance with pre-operative computed tomographic angiography (CTA) fusion and strict ALARA guidelines in a modern hybrid room. Material and methods: Between February and November 2016, consecutive patients with AAA undergoing EVAR with a bifurcated device in a hybrid room under fusion imaging guidance were prospectively enrolled in six aortic centres from the United States ( n  = 1), Europe ( n  = 4), and Japan ( n  = 1). Demographic data including body mass index (BMI), indirect dose area product (DAP), cumulative air kerma (CAK), variables influencing dose delivery, and contrast media volume were collected. Results: 85 patients (90.4% males) were included. The median age was 75 (IQR 69–81), with a median BMI of 27.4 (IQR 24.7–30.6). Median DAP and CAK were 14.7 (IQR 10.0–27.7) Gy·cm 2 and 107 (IQR 68.0–189.0) mGy, respectively. The median contrast volume was 47 mL (IQR 35–70) (equivalent to 14.1g of iodine [IQR 10.5–21.0]). Median DAP per centre was 28.1 ( n  = 16, IQR 12.6–47.1), 15.9 ( n  = 11, IQR 11.9–22.5), 14.2 ( n  = 12, IQR 10.9–25.7), 20.2 ( n  = 18, IQR 7.0–39.5), 10.3 ( n  = 27, IQR 8.2–14.7) and 26.5 ( n  = 1) Gy·cm 2 . In multivariable analysis, collimation was the only factor that was significantly associated with DAP reduction, (coefficient = −0.014 per percentage of collimation, 95% CI −0.019 to −0.008, p  < .001). Conclusions: With adherence to the ALARA principle and routine application of fusion imaging guidance for EVAR, low radiation exposure compared with the published literature can be achieved in a real world setting.